2018
DOI: 10.1002/esp.4428
|View full text |Cite|
|
Sign up to set email alerts
|

Tide‐induced bedload transport pathways in a multiple‐sand‐ridge system offshore of Hainan Island in the Beibu Gulf, northwest South China Sea

Abstract: Modern sand transport pathways in a multiple‐sand‐ridge system are elusive and have rarely been studied in recent years. We report herein a field with four en echelon linear sand ridges offshore of Hainan Island in the Beibu Gulf and describe the distribution and morphology of these sand ridges in detail for the first time. Dune crest comparisons and seismic profiles are also interpreted to assess sand transport over the dunes. Based on a Delft 3D model, regional tidal currents and tide‐induced bedload transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(125 reference statements)
1
4
0
Order By: Relevance
“…They also noted that symmetrical sand waves tend to have larger heights than asymmetrical sand waves in similar conditions. In this region, sand waves on opposite sides of a sand bank were found to migrate in opposite directions (Zhou et al, 2022), a phenomenon previously observed by Ma et al (2018).…”
Section: The Role Of Environmental Conditionssupporting
confidence: 69%
See 1 more Smart Citation
“…They also noted that symmetrical sand waves tend to have larger heights than asymmetrical sand waves in similar conditions. In this region, sand waves on opposite sides of a sand bank were found to migrate in opposite directions (Zhou et al, 2022), a phenomenon previously observed by Ma et al (2018).…”
Section: The Role Of Environmental Conditionssupporting
confidence: 69%
“…Recently, the sand waves in the South China Sea have been surveyed quite intensively (see e.g. Ma et al, 2014Ma et al, , 2018Ma et al, , 2022Zhou et al, 2018Zhou et al, , 2020Zhou et al, , 2022. These data also provide an opportunity to develop machine learning methods.…”
Section: Sand Wave Predictionsmentioning
confidence: 99%
“…What has been studied is the influence of background topography on sand wave migration: both Ma et al. (2018) and Zhou et al. (2022) observed that sand waves migrate in opposite directions on both sides of a sand bank.…”
Section: Introductionmentioning
confidence: 99%
“…So far, neither field studies nor model studies have investigated the possible connection between large-scale background topography and the degree of three-dimensionality of tidal sand waves. What has been studied is the influence of background topography on sand wave migration: both Ma et al (2018) and Zhou et al (2022) observed that sand waves migrate in opposite directions on both sides of a sand bank. Using a numerical 3D model, Leenders et al (2021) related such bi-directional migration patterns over a sand bank to alterations in residual flow patterns caused by the interaction of the tidal flow with the tidal sand bank.…”
mentioning
confidence: 99%
“…In the referenced article, Ma et al (2018), there is a clerical error in Equation (3). A minus sign was omitted, it should appear before “0.02 D*”.…”
mentioning
confidence: 99%